Modulating autophagy as a therapeutic strategy for the treatment of paediatric high‐grade glioma. (13th May 2019) - Howarth, Alison; Madureira, Patricia A.; Lockwood, George; Storer, Lisa C. D.; Grundy, Richard; Rahman, Ruman; Pilkington, Geoffrey J.; Hill, Richard
Abstract: Paediatric high‐grade gliomas (pHGG) represent a therapeutically challenging group of tumors. Despite decades of research, there has been minimal improvement in treatment and the clinical prognosis remains poor. Autophagy, a highly conserved process for recycling metabolic substrates is upregulated in pHGG, promoting tumor progression and evading cell death. There is significant crosstalk between autophagy and a plethora of critical cellular pathways, many of which are dysregulated in pHGG. The following article will discuss our current understanding of autophagy signaling in pHGG and the potential modulation of this network as a therapeutic target.